2006
DOI: 10.1002/pbc.20782
|View full text |Cite
|
Sign up to set email alerts
|

PTHrP‐independent hypercalcemia with increased proinflammatory cytokines and bone resorption in two children with CD19‐negative precursor B acute lymphoblastic leukemia

Abstract: Hypercalcemia in childhood acute lymphoblastic leukemia (ALL) is rare and occasionally associated with parathyroid hormone-related protein (PTHrP). However, the pathogenesis of PTHrP-independent hypercalcemia remains unclear. We report two children with precursor B ALL who had marked hypercalcemia (15.8 and 16.6 mg/dl, respectively) and disseminated osteolysis. Serum tumor necrosis factor-alpha (TNF-alpha) and IL-6 were markedly elevated, whereas 1,25(OH)(2) vitamin D(3), intact PTH and PTHrP were decreased or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 29 publications
0
15
0
2
Order By: Relevance
“…Moreover, calcitriol-mediated hypercalcemia, the most frequent cause of hypercalcemia in lymphoma, 4 was unlikely in these four patients. Of note, two patients (Cases 19 and 21) had B-precursor ALL with negative-or low-level expression of CD19 and their serum levels of tumor necrosis factor-a and interleukin-6, which are known to promote osteoclastic bone resorption and involve in hypercalcemia in malignancies, 28,29 were elevated at the onset of hypercalcemia, 30 representing an independent subgroup of ALL with PTHrP-independent hypercalcemia.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, calcitriol-mediated hypercalcemia, the most frequent cause of hypercalcemia in lymphoma, 4 was unlikely in these four patients. Of note, two patients (Cases 19 and 21) had B-precursor ALL with negative-or low-level expression of CD19 and their serum levels of tumor necrosis factor-a and interleukin-6, which are known to promote osteoclastic bone resorption and involve in hypercalcemia in malignancies, 28,29 were elevated at the onset of hypercalcemia, 30 representing an independent subgroup of ALL with PTHrP-independent hypercalcemia.…”
Section: Discussionmentioning
confidence: 99%
“…[94][95][96] " Unknown Gain Gain Chronic inflammation 30 " " " Loss Gain Interleukin 1 [31][32][33] " " " Loss Gain Tumor necrosis factor-a 34 The mechanisms for malignancy-associated hypercalcemia and metastatic calcification are variable but include: (1) tumor production of PTH or PTH-related peptide, vitamin D, or various cytokines; (2) upregulation of RANKL; (3) down-regulation of OPG; or (4) a combination of up-regulated RANKL and downregulated OPG. [97][98][99][100][101][102][103][104][105] Like other diseases that are associated with extraosseous mineral deposition, these cancers may be associated with simultaneous osseous mineral loss.…”
Section: Malignancy Hypercalcemia and Extraosseous Mineralizationmentioning
confidence: 98%
“…There are known humoral compounds promoting the development of hypercalcemia: prostaglandins, transforming growth factors, a number of cytokines (IL-1, IL-4, IL-6, TNF-alpha and TNF-β), which function due to activation of osteoclasts [5]. In the analysis of 23,500 proteins of human proteome, it was found that the functions of 2145 proteins depend to some extent on the level of calcium in the body (for example, the levels of protein expression change), and 625 of the 2145 proteins directly bind the Ca 2+ ion as a cofactor.…”
Section: Resultsmentioning
confidence: 99%